Інтеграція інноваційних рішень у стратегію розвитку аграрного сектору - Сєров, Іван Володимирович (Національний технічний університет "Харківський політехнічний інститут", 2024)
Стаття присвячена проблемі інтеграції інноваційних рішень у стратегію розвитку аграрного сектору, що є важливою умовою для підвищення його конкурентоспроможності та стійкості. В умовах глобалізації, змін клімату, зростання конкуренції та посилених вимог до якості продукції аграрний сектор України стикається з новими викликами. Впровадження інноваційних технологій, таких як точне землеробство, біотехнології, агродрони та цифрові платформи, сприяє підвищенню продуктивності, зниженню витрат і покращенню якості продукції. У статті розглянуто основні чинники успішного впровадження інновацій: технологічні рішення, розвиток людського капіталу, інвестиції в наукові дослідження, державна підтримка. Наголошено на важливості стратегічного підходу до інноваційного розвитку, модернізації інфраструктури та активній співпраці аграрних підприємств з науковими установами для забезпечення стійкого розвитку та адаптації до нових викликів. The article addresses the issue of integrating innovative solutions into the development strategy of the agricultural sector, which is essential for enhancing the competitiveness and sustainability of agribusinesses. The agricultural sector, being a critical part of the economy, plays a decisive role in ensuring food security and fostering the development of rural areas. In the context of globalization, climate change, intensified competition, and increasing product quality demands, agricultural enterprises face the challenge of boosting their competitiveness and resilience. The implementation of innovative technologies, such as precision farming, biotechnology, agricultural drones, and digital platforms, offers opportunities to enhance productivity, reduce resource costs, and improve product quality. Despite the scientific and practical interest in innovations in agriculture, comprehensive approaches to integrating these innovations into the strategic planning of agricultural enterprises are still underdeveloped. The article outlines the key factors for successful innovation integration: technological solutions, human capital development, investments in research and development (R&D), and government support. Technological solutions include modern technologies such as precision.
Integration of innovative solutions into the development strategy of the agricultural sector
Keywords: аграрний сектор; інновації; конкурентоспроможність; стійкість; біотехнології; цифрові платформи; модернізація інфраструктури; стратегічний розвиток; innovation; agricultural sector; competitiveness; sustainability; biotechnology; infrastructure modernization; strategic development; investment